PENGARUH PEMBERIAN INSENTIF, SEMANGAT KERJA DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA UD KABUL MIARSO BLITAR - Reza Ahmad Muhibbuddin Shofa; Kridha Hery Gunawan (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Thiis Study Aiims To Deiteirmiinei Thei Eiffeict partiially or siimultaneiously of iindeipeindeint variiableis Iinceintiivei, Work Spiiriit and Teiamwork on thei deipeindeint variiablei Eimployeiei Peirformancei at UD Kabul Miiarso Bliitar. Thiis reiseiarch useis quantiitatiivei meithods Thei reiseiarch samplei was takein usiing a saturateid sampliing teichniiquei wheirei thei eintiirei populatiion was useid as a samplei, nameily as many as 42 peioplei. Data colleictiion teichniiqueis usiing a queistiionnaiirei. Thei meithod iin thiis study useis Iinstrumeint teist and Classiical assumptiion teist, data analysiis was carriieid out by Liineiar Reigreissiion Analysiis Multiiplei and Analysiis of thei Coeiffiiciieint of Deiteirmiinatiion (R2), whiilei thei teichniiquei of teistiing thei hypotheisiis usiing thei t teist and F teist. Thei reisults of thei study show that iinceintiivei partiially havei a posiitiivei eiffeict siigniifiicant to Eimployeiei Peirformancei wiith a t count valuei of 3,004 > t tablei of 2.024 and a siig. 0,005 ? 0,05. Work Spiiriit partiially has a siigniifiicant posiitiivei eiffeict on Eimployeiei Peirformancei wiith a t count valuei of 3,030 > t tablei 2,024 and a siig. 0,004 ? 0,05. Teiamwork partiially has a siigniifiicant posiitiivei eiffeict on Eimployeiei peirformancei wiith a t count valuei of 4,426 > t tablei 2,024 and a siig. 0,000 ? 0,05. Siimultaneiously Iinceintiivei, Work Spiiriit and Teiamwork havei a siigniifiicant eiffeict on Eimployeiei Peirformancei at UD Kabul Miiarso Bliitar wiith a F count valuei of 11,413 > F tablei 2.851 and a siig. 0,000 ? 0,05